Evaluasi Kebijakan Penataan Pkl di Kawasan Alun-Alun Ngawi - Puruhita, Wahyudi (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Ngawi Government through local regulation number 6 of 2013, concerning the arrangement and the empowerment of street vendors have attempted to regulate street vendors in the Ngawi square. However, from some of these policy measures still leave the problem, because they were not optimalized yet. The purpose of this study is to evaluate the policy of street vendors arrangement in the Ngawi Square area. The street vendors evaluation process is based on the evaluation criteria such as effectiveness, efficiency, adequacy, equality, responsiveness, and accuracy. In identifying the street vendors characteristics it is used a descriptive statistical analysis. It also conducted a qualitative descriptive analysis in a review of policy matters of policy evaluation criteria to produce indicators of policy evaluation. Based on the study on policy matters structuring vendors have fulfilled the criteria of effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. However, based on the data achievements, these criteria are still not optimally fulfilled, except the accuracy criterion. In order to fulfill these criteria, it is necessary to be followed-up by the government in the term of a firmness in a data collection and a control of the vendors, a maturity and an openness in the planning of street vendors infrastructures, and strengthening the cooperation of government institutions. Actions should be taken by the traders are an active participation and an awareness in maintaining the Ngawi square.